Érosion des normes et avenir des institutions états-uniennes - Anne Deysine (Revue LISA)
This article shows how the system of checks and balances put in place by the Founding fathers failed to stop the many attacks by President Donald Trump against the rule of law in general and more specifically the liberty of the press and the independence of the judiciary (including law enforcement). The result is an erosion of written norms (article III, First Amendment, emoluments clause) and of unwritten norms. Among the latter, the refusal to publish his income tax return and to avoid conflicts of interests (and the appearance of conflicts of interests) by placing his holdings in a blind trust. The result is both a deterioration of US institutions and values and a shift towards an illiberal democracy.